High-resolution AMI Large Array imaging of spinning dust sources: spatially correlated 8 µm emission and evidence of a stellar wind in L675 - Scaife, A.; Green, D.; Pooley, G.; Davies, M.; Franzen, Thomas; Grainge, K.; Hobson, M.; Hurley-Walker, Natasha; Lasenby, A.; Olamaie, M.; Richer, J.; Rodriguez-Gonzalvez, C.; et al. (Wiley-Blackwell Publishing Ltd., 2010)
We present 25 arcsec resolution radio images of ?ve Lynds Dark Nebulae (L675, L944, L1103,L1111 and L1246) at 16 GHz made with the Arcminute Microkelvin Imager (AMI) LargeArray. These objects were previously observed with the AMI Small Array to have an excessof emission at microwave frequencies relative to lower frequency radio data. In L675, we ?nda ?at spectrum compact radio counterpart to the 850µm emission seen with SubmillimetreCommon-User Bolometer Array (SCUBA) and suggest that it is cm-wave emission from apreviously unknown deeply embedded young protostar. In the case of L1246, the cm-waveemission is spatially correlated with 8µm emission seen with Spitzer. Since the mid-infraredemission is present only in Spitzer band 4 we suggest that it arises from a population ofpolycyclic aromatic hydrocarbon molecules, which also give rise to the cm-wave emissionthrough spinning dust emission.